Korean guidelines for postpolypectomy colonoscopic surveillance: 2022 revised edition - Su Young Kim; Min Seob Kwak; Soon Man Yoon; Yunho Jung; Jong Wook Kim; Sun-Jin Boo; Eun Hye Oh; Seong Ran Jeon; Seung-Joo Nam; Seon-Young Park; Soo-Kyung Park; Jaeyoung Chun; et al. (Korean Society of Gastrointestinal Endoscopy, 2022)
Colonoscopic polypectomy is effective in decreasing the incidence and mortality of colorectal cancer (CRC). Premalignant polyps discovered during colonoscopy are associated with the risk of metachronous advanced neoplasia. Postpolypectomy surveillance is the most important method for the management of advanced metachronous neoplasia. A more efficient and evidence-based guideline for postpolypectomy surveillance is required because of limited medical resources and concerns regarding colonoscopy complications. In these consensus guidelines, an analytic approach was used to address all reliable evidence to interpret the predictors of CRC or advanced neoplasia during surveillance colonoscopy. The key recommendations state that the high-risk findings for metachronous CRC following polypectomy are as follows: (1) adenoma ≥10 mm in size; (2) 3 to 5 (or more) adenomas; (3) tubulovillous or villous adenoma; (4) adenoma containing high-grade dysplasia; (5) traditional serrated adenoma; (6) sessile serrated lesion (SSL) containing any grade of dysplasia; (7) serrated polyp of at least 10 mm in size; and (8) 3 to 5 (or more) SSLs. More studies are needed to fully comprehend the patients most likely to benefit from surveillance colonoscopy and the ideal surveillance interval to prevent metachronous CRC.